The Influence of Emotional Intelligence and Spiritual Intelligence on the Performance of Lecturers at Nalanda Institute - Kelvin Kelvin; Khie Khiong; Budi Utomo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Efforts to improve educational quality include various policy measures and programs, such as increasing educational access, improving curricula, and enhancing the quality of teachers and lecturers.The aim of this study is to determine the extent of the influence of emotional intelligence and spiritual intelligence on the performance of lecturers at Institut Nalanda. The methodology used is quantitative with multiple regression analysis, involving a population of 34 respondents and a sample size of 34 lecturers from Institut Nalanda. The results of this study indicate that emotional intelligence has an impact of 61.6% on lecturer performance; spiritual intelligence is shown to contribute 64.9% to lecturer performance; and both emotional intelligence and spiritual intelligence together have an impact of 61.6% on lecturer performance.